1996
DOI: 10.1002/(sici)1097-4644(19961101)63:2<185::aid-jcb6>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression of extracellular matrix components in dilated cardiomyopathy

Abstract: Extracellular matrix metalloproteinases (MMPs) are activated in dilated cardiomyopathic (DCM) hearts [Tyagi et al. (1996): Mol Cell Biochem 155:13-21]. To examine whether the MMP activation is occurring at the gene expression level, we performed differential display mRNA analysis on tissue from six dilated cardiomyopathy (DCM) explanted and five normal human hearts. Specifically, we identified three genes to be induced and several other genes to be repressed following DCM. Southern blot analysis of isolated cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
55
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 35 publications
5
55
1
Order By: Relevance
“…10,11,27 For example, Weber et al 10 reported alterations in the myocardial fibrillar collagen architecture in patients with DCM. Tyagi et al 15 reported increased collagen degradation products in DCM myocardial samples, providing evidence for increased collagen degradation. More recently, several studies have demonstrated increased myocardial MMP zymographic activity in patients with DCM.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…10,11,27 For example, Weber et al 10 reported alterations in the myocardial fibrillar collagen architecture in patients with DCM. Tyagi et al 15 reported increased collagen degradation products in DCM myocardial samples, providing evidence for increased collagen degradation. More recently, several studies have demonstrated increased myocardial MMP zymographic activity in patients with DCM.…”
Section: Discussionmentioning
confidence: 97%
“…[12][13][14][15] More importantly, MMPs have been shown to be upregulated in various disease states. [13][14][15][16][17]26 The relation between MMP activity and MMP and TIMP species abundance in LV myocardium in the setting of idiopathic DCM remained unexplored. Accordingly, this study examined MMP activity and MMP and TIMP abundance in normal and DCM human LV myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations